FROM FOSSIL FUELS TO RENEWABLE ENERGY: TRACKING BULGARIA’S TRANSITION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The report examines Bulgaria’s progress in transitioning from fossil fuels to renewable energy sources. It analyses the achievements and challenges faced by the country in this process. Recent changes in Bulgaria's energy mix, with a focus on the growth of renewable energy capacity, are discussed. The report outlines the achievements of Bulgaria's energy transition and emphasizes the importance of diversifying the energy mix. In addition, the challenges faced by the country in this transition are also addressed. The significance of factors such as policy and regulatory issues, economic and social considerations, technological and climate limitations is also highlighted. The research methods used include a review and analysis of relevant literature, examination of statistical data and reports from energy authorities, and interviews with experts in the field. This approach allows for a comprehensive understanding of Bulgaria's transition to renewable energy. The report draws conclusions on the performance of the sector and emphasizes the importance of different energy sources for the security and reliability of the electricity system and identifies key areas for further improvement.